Probiotics: A Treatment Alternative for Dermatological Diseases Exacerbated During COVID-19 Pandemic - Abril Morales (Journal of Medical Biomedical and Applied Sciences, 2021)
The COVID-19 pandemic generated stress situation on the world population and the mandatory adoption of personal protective equipment, especially the use of a mask to avoid possible infections. This caused the exacerbation of dermatological diseases such as acne, rosacea, atopic dermatitis and psoriasis. Several measures have been developed to prevent and treat this kind of dermatology conditions, suggesting probiotics as an alternative and adjuvant in its treatment, acting as immunomodulators and improving cutaneous dysbiosis.